Indonesia's Strategy in Response to COVID-19: A Fragmented State Balancing Health and Economy - Yohanes William Santoso (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
This article aims to explain how the country's transformation influences Indonesia's strategy in dealing with the COVID-19 pandemic. Taking a period from March 2020 to May 2022, this article is based on the strategy of the Indonesian government, which seeks to balance health and economic aspects when responding to a pandemic. Indonesia has chosen an adaptive balancing strategy that balances health and economic aspects to respond to the pandemic. This strategy is relatively different from the reference strategy suggested by the World Health Organization (WHO), which focuses more on health before recovering the economy, which has drawn criticism from various experts. Nevertheless, the Indonesian government's efforts to deal with the pandemic have experienced significant progress and have succeeded in reducing transmission rates and accelerating vaccination. Therefore, this research explains why Indonesia chose an adaptive balancing strategy. To answer this question, researchers use state transformation theory as an explanatory instrument in understanding the dynamics of the policy-making process at the domestic level in response to a pandemic. In particular, the findings of this article discuss how fragmentation in Indonesia explains the domestic dynamics behind the country's response to cross-border non-traditional security issues such as the COVID-19 pandemic. Keywords: Indonesia, Adaptive Balancing Strategy, COVID-19 Pandemic, State Transformation, Fragmentation Artikel ini bertujuan untuk menjelaskan bagaimana transformasi negara memengaruhi strategi Indonesia dalam menghadapi pandemi COVID-19. Dengan mengambil jangka waktu mulai dari Maret 2020 hingga Mei 2022, artikel ini berlatar belakang pada strategi pemerintah Indonesia yang berupaya untuk menyeimbangkan antara aspek kesehatan dan perekonomian ketika merespons pandemi. Indonesia memilih strategi perimbangan adaptif yang menyeimbangkan aspek kesehatan dan ekonomi sebagai jalan keluar dalam merespons pandemi. Strategi tersebut relatif berbeda dengan acuan strategi yang disarankan oleh World Health Organization (WHO) yang lebih berfokus pada kesehatan sebelum memulihkan perekonomian sehingga sempat menuai kritik dari berbagai pakar. Walaupun demikian, upaya pemerintah Indonesia dalam menangani pandemi mengalami perkembangan yang signifikan dan berhasil menurunkan angka penularan serta mempercepat vaksinasi. Oleh karena itu, penelitian ini berusaha menjelaskan alasan mengapa Indonesia memilih strategi perimbangan adaptif. Untuk menjawab pertanyaan tersebut, peneliti menggunakan teori transformasi negara sebagai instrumen penjelas dalam memahami dinamika proses pengambilan kebijakan di tingkat domestik untuk merespons pandemi. Secara khusus, temuan artikel ini membahas bagaimana fragmentasi di Indonesia menjelaskan dinamika domestik di balik respons negara terhadap isu keamanan non-tradisional lintas batas seperti pandemi COVID-19. Kata-kata kunci: Indonesia, Strategi Perimbangan Adaptive, Pandemi COVID-19, Transformasi Negara, Fragmentasi